Efforts to Improve Teacher Discipline and Performance Through Peko: Regulations and Commitments - Sugianingsih, Juli; Nugraha, Nurhadji; Hartono, Yudi (Newinera Publisher, 2025)
This study aims to analyze the implementation of the PEKO (Regulations and Commitments) strategy in improving teacher and educational staff discipline and performance at SD Negeri 02 Madiun Lor, Manguharjo District, Madiun City in 2025. The research employs a descriptive qualitative approach with data collected through observation, in-depth interviews, and document studies. The results indicate that the PEKO model effectively integrates structural and motivational dimensions in human resource management within educational institutions. The enforcement of clear regulations such as digital attendance, uniform compliance, and daily duty schedules—significantly increased discipline levels, while continuous coaching, transformational leadership, and proportional reward–punishment systems strengthened commitment and intrinsic motivation. The findings show an improvement in teacher attendance from 87% to 98%, enhanced teaching preparation, and more professional school culture. The principal’s exemplary leadership played a key role in fostering collaboration, transparency, and collective accountability. In conclusion, the PEKO strategy successfully transformed the work culture from loose and individualistic into professional, orderly, and collaborative, providing a sustainable model for enhancing educational quality through disciplined and committed human resources.